2010
DOI: 10.1007/s11103-010-9644-1
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and transcriptional analyses of reduced zein kernels derived from the opaque2 mutation and RNAi suppression

Abstract: Corn protein is largely made up of a group of nutritionally limited storage proteins known as zein. The reduction of zein can be achieved by a transcriptional mutation, opaque2 (o2), or a transgene targeting zein through RNA interference (RNAi). Zein reduction results in an increase of more nutritionally balanced non-zein proteins, and therefore enhance the overall quality of corn protein. In this study, the composition of mature kernels and the transcriptional profile of developing kernels of these two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 46 publications
4
41
1
Order By: Relevance
“…LKR/SDH, which encodes a bifunctional enzyme involved in Lys catabolism (Kemper et al, 1999), is also regulated by O2. Gene expression profiling analysis of o2 mutants revealed that O2 regulates transcription of many genes involved in a variety of pathways (Frizzi et al, 2010;Hartings et al, 2011;Hunter et al, 2002;Jia et al, 2007;Jia et al, 2013), which is consistent with the described pleiotropic effects of the mutant.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…LKR/SDH, which encodes a bifunctional enzyme involved in Lys catabolism (Kemper et al, 1999), is also regulated by O2. Gene expression profiling analysis of o2 mutants revealed that O2 regulates transcription of many genes involved in a variety of pathways (Frizzi et al, 2010;Hartings et al, 2011;Hunter et al, 2002;Jia et al, 2007;Jia et al, 2013), which is consistent with the described pleiotropic effects of the mutant.…”
Section: Introductionsupporting
confidence: 78%
“…To provide a more detailed understanding of O2-regulated gene expression, profiling studies based on microarray analysis were performed that revealed multiple DEGs in o2 endosperm (Hunter et al, 2002;Jia et al, 2007;Frizzi et al, 2010;Hartings et al, 2011;Jia et al, 2013). These studies showed that, along with 22-kD a-zeins and the 14-kD b-zein, a number of other zein genes, e.g., 19-kD a-zeins and the 10-kD d-zein, also showed decreased transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of RNA and Selected B-box Gene Expression Analysis-RNA was prepared according to a modified method as described previously (18). Briefly, field-grown soybean (R5) leaf tissue samples were taken from 3 a.m. to 3 p.m. at 3-h intervals and flash-frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…1) (Li et al 2014; Schmidt et al 1990). Previous studies showed that O2 directly regulates many target genes associated with storage functions, including zeins, through binding to a number of conserved cis -motifs collectively known as the O2 box (Cord Neto et al 1995; Frizzi et al 2010; Hartings et al 2011; Hunter et al 2002; Jia et al 2007, 2013; Li et al 2015; Muth et al 1996; Schmidt et al 1987, 1990, 1992; Zhang et al 2015, 2016). Thus far, a number of protein partners of O2 have been identified that include both annotated TFs [e.g., the PROLAMIN-BOX BINDING FACTOR (PBF), the O2-heterodimerizing proteins (OHP1 and OHP2), MADS47, ALTERATION/DEFICIENCY IN ACTIVATION2 (ADA2)] and non-TF proteins [e.g., Taxilin and GENERAL CONTROL OF NITROGEN5 (GCN5)] (Bhat et al 2004; Hwang et al 2004; Jin et al 2014; Pysh et al 1993; Pysh and Schmidt 1996; Qiao et al 2016; Vicente-Carbajosa et al 1997; Wang et al 1998; Yilmaz et al 2009; Zhang et al 2012).…”
Section: Mutations In Regulatory Genes Associated With Endosperm Stormentioning
confidence: 99%
“…As mentioned above, a key subset of target genes includes the zein multi-gene family. Mutations in or down-regulation of some zein genes can improve the lysine deficiency of wild-type maize, and thereby increase its nutritional quality (Frizzi et al 2010; Hunter et al 2002). The LKR/SDH gene encoding a lysine-ketoglutarate reductase/saccharopine dehydrogenase is activated by O2 (Kemper et al 1999).…”
Section: Mutations In Regulatory Genes Associated With Endosperm Stormentioning
confidence: 99%